Chicken chicken - Stine, R. L. (New York : Scholastic, 2007)
Cole and Crystal learn a lesson about the importance of good manners when they have a run-in with weird Vanessa, Goshen Falls's resident sorceress.
3.5
5-8
Keywords: Brothers and sisters -- Juvenile fiction; Chickens -- Juvenile fiction; Magic -- Juvenile fiction; Brothers and sisters -- Fiction; Chickens -- Fiction; Horror stories; Magic -- Fiction; Chickens -- Fiction; Horror fiction; Magic -- Fiction; Siblings -- Fiction; Horror fiction